Introduction of a triphenylamine substituent on pyridyl rings as a springboard for a new appealing brightly luminescent 1, 3-di-(2-pyridyl)benzene platinum(ii) complex family. Issue 32 (25th July 2022) - Colombo, Alessia; De Soricellis, Giulia; Fagnani, Francesco; Dragonetti, Claudia; Cocchi, Massimo; Carboni, Bertrand; Guerchais, Véronique; Marinotto, Daniele
Abstract : A novel luminescent platinum(ii ) complex family characterized by a long lifetime and a high quantum yield in the yellow-green or NIR region depending on the concentration. Abstract : The preparation and characterization of three new complexes, namely [Pt(1, 3-bis(4-triphenylamine-pyridin-2-yl)-4, 6-difluoro-benzene)Cl] ([PtL 1 Cl] ), [Pt(1, 3-bis(4-triphenylamine-pyridin-2-yl)-5-triphenylamine-benzene)Cl] ([PtL 2 Cl] ), and [Pt(1, 3-bis(4-triphenylamine-pyridin-2-yl)-5-mesityl-benzene)Cl] ([PtL 3 Cl] ), is reported. All of them are highly luminescent in dilute deaerated dichloromethane solution ( Φ lum = 0.88–0.90, in the yellow-green region; the λ max, em in nm for the monomers are: 562, 561 and 549 for [PtL 1 Cl], [PtL 2 Cl] and [PtL 3 Cl], respectively).[PtL 1 Cl] is the most appealing, being characterized by a very long lifetime (103.9 μs) and displaying intense NIR emission in concentrated deaerated solution ( Φ lum = 0.66) with essentially no "contamination" by visible light < 600 nm. This complex allows the fabrication of both yellow-green and deep red/NIR OLEDs; OLED emissions are in the yellow-green (CIE = 0.38, 0.56) and deep red/NIR (CIE = 0.65, 0, 34) regions, for [PtL 1 Cl] 8 wt% (with 11% ph/e EQE) and pure [PtL 1 Cl] (with 4.3% ph/e EQE), respectively.